The Impact of High Salt Diet on the Nociceptive Pain Thresholds and Functional Phenotype of Myeloid Cells - Anni Fan; Xiang Qun Shi; Ji Zhang (Taylor & Francis Group, 2019)
Introduction/Aim: Though several studies have shown that high salt diet (HSD) is related to the development of chronic diseases, the effect of long-term high-salt intake on the immune system and pain behavior remains elusive. Here, we aimed to investigate whether and how HSD affected mouse pain thresholds and innate immunity, especially myeloid cells. Methods: Healthy C57BL/6 male and female mice were fed with HSD (containing 4% NaCl in chow and 1% NaCl in water) right from weaning period (3-week after birth) for 1-3 months. Results: Behavioral analysis demonstrated that HSD-fed mice were hypersensitive to mechanical stimuli. Moreover, HSD induced an expansion of circulating monocytes, especially the proinflammatory monocyte (Ly6Chigh, CCR2+) subsets. HSD also increased the density of Iba-1+ microglia and the number of FcγII/III receptor (CD16/32) expressing cells in the lumbar spinal cord. Prolonged HSD feeding, meanwhile, resulted in increased infiltration of monocyte to the peripheral nerves, contributing to the monocyte-derived macrophage (CD11b+, F4/80+) population. Finally, shifting the HSD back to the regular laboratory chow (with 0.3% NaCl) cannot reverse the HSD-induced mechanical hypersensitivity myeloid cell expansion and polarization towards the inflammatory subsets in the periphery. However, treating HSD mice with CCR2 antagonist effectively normalized the pain threshold and myeloid cell profile in the peripheral blood and nerves. Discussion/Conclusions: Long term HSD feeding decreased mouse mechanical thresholds, in parallel with an expansion and polarization of myeloid cells towards inflammatory status. Such changes were not reversible when HSD-fed mice back to normal diet. However, blocking CCR2 signaling successfully attenuated HSD-induced hypersensitivity.